2022
DOI: 10.1101/2022.09.13.507868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusible fraction of niche BMP ligand safeguards stem-cell differentiation

Abstract: Drosophila male germline stem cells (GSCs) reside at the tip of the testis and surround a cluster of niche cells, called the hub. It has been believed that the Decapentaplegic (Dpp) ligand, secreted from the hub, only activates stem cells in close proximity, but not differentiating cells spaced one-cell layer away. However the range of Dpp diffusion is unknown. Here, using genetically encoded nanobodies, called Morphotrap, we physically block Dpp diffusion outside of the niche without interfering with niche-st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Using the mGL-dpp allele also allows for visualization of the extracellular Dpp distribution through anti-GFP antibody staining. FRAP assays, morphotrap, and live imaging have already been successfully applied to characterize the role of mGL-Dpp in the Drosophila 43 . By applying these assays in the wing disc, it would be of interest to re-investigate the kinetics of Dpp morphogen gradient formation under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Using the mGL-dpp allele also allows for visualization of the extracellular Dpp distribution through anti-GFP antibody staining. FRAP assays, morphotrap, and live imaging have already been successfully applied to characterize the role of mGL-Dpp in the Drosophila 43 . By applying these assays in the wing disc, it would be of interest to re-investigate the kinetics of Dpp morphogen gradient formation under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To determine which BMP ligand(s) signal to Sax to maintain spermatid bundling, we first investigated Gbb as Sax preferentially binds Gbb, and Gbb is known to be expressed in CCs in the testis [5,19]. We knocked down Gbb in CCs under the c587Gal4 driver combined with TubGal80 ts .…”
Section: Soma (Cc)-derived Gbb Signals To the Germline To Maintain Pr...mentioning
confidence: 99%
“…Recent work has demonstrated that Dpp can freely diffuse from the hub, and this diffusible fraction of Dpp signals in a different manner than contact-dependent Dpp signaling at Hub-GSC interface [5]. Diffusible Dpp signals through either of the type I receptors Tkv or Saxophone (Sax) and the type II receptor Punt on gonialblasts (GBs) and spermatogonia (SGs) to upregulate Bam expression and prevent differentiating cells from returning to the niche through dedifferentiation [5]. Moreover, expression of Bam is known to regulate the number of transit amplifying SG divisions [6].…”
Section: Introductionmentioning
confidence: 99%
“…[83] While nichederived Dpp was thought to act in a short-range manner to maintain male germline stem cells (GSCs) in Drosophila, blocking endogenous Dpp spreading revealed an unexpected role of a diffusive fraction of Dpp in differentiating cells further away from the source. [84] Replacing endogenous Wnt3a with a receptor-fused form that activates signaling only in producing cells in mice increased heterogeneity in Wnt signaling and sensitivity to retinoic acid, an endogenous antagonist of neuromesodermal progenitor (NMP) maintenance, indicating that intercellular exchange of Wnt ligands reduces cell population heterogeneity and achieves robustness to environmental stress in NMP cells. [85] It would be therefore interesting to reinvestigate how morphogens act using protein binder tools.…”
Section: Biological and Experimental Relevance For Other Morphogen Sy...mentioning
confidence: 99%